Integration of AI and Adaptive Microfinance in Islamic Banking for Maqashid Sharia-Based Financial Inclusion: A Conceptual Framework - Misi Anggraini; Muchlis Bahar; Duhriah; Yulizain Putra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Background: Digital transformation and artificial intelligence (AI) are reshaping Islamic banking, creating opportunities to improve financial inclusion while adhering to Maqashid Sharia. Objective: This study develops a conceptual framework integrating AI and adaptive microfinance to promote Maqashid Sharia-based financial inclusion in Islamic banking. Methodology: A qualitative conceptual approach was employed through a comprehensive literature review and policy analysis of studies on AI, adaptive microfinance, Islamic banking, and financial inclusion. Findings: The proposed framework suggests that AI can improve financing assessment, operational efficiency, risk management, and access to financial services for underserved communities. Combined with adaptive microfinance, AI supports the achievement of Maqashid Sharia by enhancing social welfare, protecting wealth, promoting equitable economic opportunities, and reducing poverty. The analysis also identifies key challenges, including regulatory constraints, limited Sharia-compliant digital expertise, algorithmic bias, data privacy, and institutional coordination. Novel Contribution: This study proposes the AI-Based Adaptive Islamic Microfinance Framework, integrating AI, adaptive microfinance, and Maqashid Sharia into a unified conceptual model. Practical Implication: The framework offers strategic guidance for Islamic banks, regulators, and policymakers while providing a foundation for future empirical research